THE INFLUENCE OF COOPERATIVE LEARNING MODELS HELPED MEDIA BASED ON VIDEO EXPLAINER AGAINST STUDENT LEARNING RESULTS OF CLASS X IPS MAN 1 SAMARINDA - Tiara Risqi; Sudarman Sudarman; Ratna Fitri Astuti (Educational Studies: Conference Series, 2022)
One of the factors that cause low student learning outcomes is that students do not understand the material givenduring the learning process. This research aims toto find out the Effect of Cooperative Learning Learning Model Assisted by Media-Based Video Explainer on Student Learning Outcomes of Class X Social Sciences MAN 1 Samarinda. This research is a quantitative research with a quasi-experimental type of research with the research subjects of class X IPS MAN 1 samarinda students, namely in class X-1 as many as 34 people as control class and X-4 as many as 34 people as experiment class.Data collection was carried out using test techniques. The research hypothesis was tested using the t-test Independent Samples t-Test. The results showed that the value of tcount > ttable was 3,554 > 1,693, so H0 was rejected and Ha was accepted. So it can be concluded that there is a significant effect of the cooperative learning model assisted by media based on explainer videos on the learning outcomes of students in class X IPS MAN 1 Samarinda.